2012
DOI: 10.3171/2012.10.focus12305
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of physician-observed concussion during a varsity university hockey season: metabolic changes in ice hockey players. Part 4 of 4

Abstract: Object Despite negative neuroimaging findings using traditional neuroimaging methods such as MRI and CT, sports-related concussions have been shown to cause neurometabolic changes in both the acute and subacute phases of head injury. However, no prospective clinical study has used an independent physician-observer design in the monitoring of these changes. The objective of this study was to evaluate the effects of repetitive concussive and sub-concussive head impacts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 30 publications
0
51
0
Order By: Relevance
“…51,53,57 Repeated or follow-up MRS was conducted in five of the 11 identified studies. 51,53,54,57,58 Three of five of these studies reported significantly decreased levels of NAA in the DLPFC and M1, 50 and the frontal cortical-subcortical juncture, 53,57 and decreased Glu and mI in the M1. 50 More specifically, Henry and coworkers 51 reported persisting decreases in NAA:Cr levels in the DLPFC over time (6 month post-injury follow-up), decreased levels of Glu:Cr in the M1 in the acute phase but recovery in the chronic phase, and equivalent mI:Cr levels in the acute phase but significant differences emerged over time.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…51,53,57 Repeated or follow-up MRS was conducted in five of the 11 identified studies. 51,53,54,57,58 Three of five of these studies reported significantly decreased levels of NAA in the DLPFC and M1, 50 and the frontal cortical-subcortical juncture, 53,57 and decreased Glu and mI in the M1. 50 More specifically, Henry and coworkers 51 reported persisting decreases in NAA:Cr levels in the DLPFC over time (6 month post-injury follow-up), decreased levels of Glu:Cr in the M1 in the acute phase but recovery in the chronic phase, and equivalent mI:Cr levels in the acute phase but significant differences emerged over time.…”
Section: Resultsmentioning
confidence: 94%
“…49 Two of 11 studies involved only male samples, 50,51 2 studies did not report on sex, 49,52 and 1 did not report on sex for the control group. 53 Of the seven studies that included a mixture of both exess, five reported on the sex split in athletes 54 and controls, [55][56][57] whereas the other two studies reported on the overall sample only. 53,58 In total, of the studies identifying sex, 219 males and 95 females were represented in the overall sample.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Reductions in NAA have been reported within 72 h of a head injury, with complete recovery noted by day 30 [23]. NAA reductions have also been identified in female collegiate hockey players over the course of the season, with no such similarities in the male group [24]. Longterm changes in brain chemistry have also been identified in a group of former college athletes with a known history of concussion [25].…”
Section: Imaging/vascularmentioning
confidence: 92%